2022
DOI: 10.1002/jcla.24773
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and clinical characteristics of Clostridioides difficile infection in patients with inflammatory bowel disease from a teaching hospital

Abstract: Background Clostridioides difficile infection (CDI) in patients with inflammatory bowel disease (IBD) is of increasing concern. This study aimed to investigate the molecular epidemiology and antimicrobial susceptibilities of toxigenic C. difficile isolated from IBD patients and to evaluate the risk factors for CDI in IBD population. Methods Loose or watery stools from IBD patients were tested for glutamate dehydrogenase, C. difficile toxins A&B and anaerobic culture. Toxigenic C. difficile isolates were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…C. difficile infections can trigger flares of IBD and worsen the disease course[ 42 , 43 ]. A recent study suggested PPI use as an independent risk factor for C. difficile infection in IBD patients[ 44 ]. Multiple mechanisms may underlie this association.…”
Section: Mechanisms For Potential Effects Of Ppis On Ibdmentioning
confidence: 99%
“…C. difficile infections can trigger flares of IBD and worsen the disease course[ 42 , 43 ]. A recent study suggested PPI use as an independent risk factor for C. difficile infection in IBD patients[ 44 ]. Multiple mechanisms may underlie this association.…”
Section: Mechanisms For Potential Effects Of Ppis On Ibdmentioning
confidence: 99%